Electrostimulation in sports and rehabilitation - Helmut Kern (PAGEPress Publications, 2011)
The known effects of Neuromuscular Electrical Stimulation (NMES) in Sports and Physical Medicine and Rehabilitation are presented in a review of literature. Influences of NMES on strength, endurance, neural adaptations, therapy of edema and pain as well as functional improvements will be focused on. Basics of physiology and histology in human muscle tissues are discussed in depth as well as elementary knowledge of NMES derived from animal studies. The central topic of this review is the influence of NMES on human skeletal muscle regarding histological changes, fiber transformation as well as strength and endurance of muscles involved. We optimized NMES characteristics and then conducted a series of investigations with 9 volunteers that had 30 minutes of NMES applied twice daily for 7 weeks. Muscle biopsies were taken from the vastus lateralis portion of quadriceps femoris muscle on both the stimulated and no stimulated leg before and after the 7 week NMES period. Additionally participants performed isometric strength measurements of quadriceps femoris muscle at different knee joint angles before and after the 7 week stimulation period. Biopsies from the no stimulated side showed no significant changes and may therefore serve as proof for the quality of the biopsies and as a standard for comparison. The increment of type IIa fiber volume was 12.3% and of type IIa fiber number 16%, respectively. Volume density of intermyofibrillar mitochondria increased by 22%. Subsarcolemmal mitochondria remained unchanged which contrasts the effects seen in voluntary non-NMES muscle training. Capillary density was augmented by 14.58%. NMES is an appropriate means of adjusting longstanding muscle dysbalance regarding strength, endurance and improving oxidative metabolism in human skeletal muscle. Daily muscle fiber workload (i.e. number of stimuli per day) was found to be the main determinant of fiber transformation.